Kebijakan Diversi terhadap Anak yang Berkonflik dengan Hukum dan Diancam dengan Pidana 7 (Tujuh) Tahun Berlandaskan Keadilan - Ismail Pettanase; Dea Justicia Ardha (Universitas Batanghari Jambi, 2022)
The problem of criminal acts committed by children is now increasing in society, both in developed and developing countries. Such developments are also underway in Indonesia with the integration of the value system characterized by an industrial society, the clash between traditional local values and the values of modernism is inevitable. In the end, the most pronounced impact as a result of the very rapid social change towards industrial life is the deviation of the behavior of children or adolescents. The problem that the author raises in this paper is how is the diversion policy for children who are in conflict with the law in criminal cases that are threatened with a 7 (seven) year sentence based on the value of justice? The diversion policy for children who are in conflict with the law who are threatened with a sentence of 7 (seven) years based on the value of justice is limited by the existence of Article 7 paragraph (2) letters a and b which states that diversion is carried out in the event that the crime committed is threatened with imprisonment under 7 (seven) years. The existence of Article 7 paragraph (2) letters a and b has limited the implementation of the diversion itself, and this is clearly contrary to the principles of the holding of the child protection law. The existence of restrictions has hurt the best principle for the child. The reason that can be stated that the diversion is the transfer of the settlement process to avoid stigma on the child and the diversion is not automatically acceptable to both parties, namely the victim and the perpetrator, so that even though the sanctions imposed are 7 years old, there is still the possibility of unsuccessful diversion and vice versa even though the criminal sanctions are above 7 years, it is possible that the diversion can be successful. The method that the author uses is the normative research method, namely by looking at the law as a rule (norm).